The Impact of Controlson Capital Movementson the Private Capital Accounts of Countries' Balance of Payments : Empirical Estimates and Policy Implications - Johnston, R. (IMF Working Papers; Working Paper, 1994)
This paper reports research on the impact of controls on capital movements on the private capital accounts of countries' balance of payments using data drawn from 52 countries for the period 1985-92. The results indicate that: (1) capital controls operated by developing countries have not been effective in insulating the private capital accounts of these countries' balance of payments, and (2) capital controls operated by industrial countries significantly affected the structure of their capital flows mainly by inhibiting net foreign direct and portfolio investment outflows. The results, which are consistent with other observations, raise issues for the policy toward the maintenance and liberalization of controls on capital movements by developing countries.